1999
DOI: 10.1111/1469-8986.3660699
|View full text |Cite
|
Sign up to set email alerts
|

The effects of threat and nonthreat word lead stimuli on blink modification

Abstract: Two experiments examined the effects of visually presented threat and nonthreat word lead stimuli on blink modification among unselected young adults (Experiment 1, N = 35) and participants selected for low and high trait anxiety (Experiment 2, N = 60). The blink reflex was elicited by a white noise probe of 105 dB. Lead stimulus intervals of 60, 120, 240, and 2000 ms were used in both experiments. Prepulse inhibition was observed at the 240-ms interval and prepulse facilitation was observed at the 60-ms inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
27
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 29 publications
9
27
2
Order By: Relevance
“…No significant inhibition was found at 60 ms, replicating results from previous studies (Aitken et al 1999;Lipp et al 2001). These authors found that acoustic blink was facilitated if elicited 60 ms after the onset of a visual lead stimulus, suggesting a lack of selective attention effects on blink modulation at 60 ms. A similar conclusion was reached by Dawson et al (1989), who showed that PPI to a 60-ms lead prepulse was not affected by selective attention.…”
Section: Discussionsupporting
confidence: 90%
“…No significant inhibition was found at 60 ms, replicating results from previous studies (Aitken et al 1999;Lipp et al 2001). These authors found that acoustic blink was facilitated if elicited 60 ms after the onset of a visual lead stimulus, suggesting a lack of selective attention effects on blink modulation at 60 ms. A similar conclusion was reached by Dawson et al (1989), who showed that PPI to a 60-ms lead prepulse was not affected by selective attention.…”
Section: Discussionsupporting
confidence: 90%
“…Second, and in line with previous studies probing startle modulation during viewing of emotional pictures and unpleasant words (e.g., Bradley et al, 2006;Aitken et al, 1999;Waters et al, 2000), motivational priming effects occurred during shallow processing only. Given that picture viewing and shallow processing of words are perceptual tasks, our findings support the notion that motivational priming accounts for modulation of the startle during perceptual processing of affective stimuli (e.g., Bradley et al, 1990Bradley et al, , 2001Cuthbert et al, 1998;Filion et al, 1993), that is when attention is captured automatically by emotional stimuli (e.g., Herbert et al, 2008;Kissler et al, 2007;Schupp et al, 2004Schupp et al, , 2006.…”
Section: Discussionsupporting
confidence: 85%
“…This startle response modulation by emotional valence has been proposed to reflect a general principle of motivational response organization, priming and preparing the mobilization of defensive responses during confrontation with aversive stimuli and inhibiting defensive reactions to stimuli signalling approach and reward (Lang, 1995;Lang et al, 1997). In line with this assumption, motivational priming of the startle reflex has been replicated many times during viewing of emotionally evocative picture stimuli Lang, 2000, andLang et al, 1997 for an overview) and blink potentiation during viewing of threat-related and disorder-relevant words has been demonstrated in three recent-studies (Aitken et al, 1999;Hazlett et al, 2007;Waters et al, 2000). Nevertheless, the full pattern of emotional priming during word processing, including blink inhibition during viewing of pleasant words, has not been demonstrated before.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The startle response, as measured by the eye blink latency and magnitude, is potentiated by the fear state induced through conditioning. The response has been potentiated by darkness in adults and children , threat of shock (Funayama et al, 2001), aversive airpuff (Grillon & Ameli, 1998;, lighting conditions (Basso, 2001), context conditioning (Ameli et al, 2001), emotionally laden word presentation (Aitken et al, 1999) and emotional pictures Lang et al, 1990). In addition, potentiated startle research has also demonstrated enhanced startle responses in individuals with anxiety disorders.…”
Section: Introductionmentioning
confidence: 99%